2016
DOI: 10.1111/cyt.12317
|View full text |Cite
|
Sign up to set email alerts
|

Triage of LSIL/ASC-US with p16/Ki-67 dual staining and human papillomavirus testing: a 2-year prospective study

Abstract: Objective: To investigate human papillomavirus (HPV) DNA testing and p16/Ki-67 staining for detecting cervical intraepithelial grade 2 or worse (CIN2+) and CIN3 in women referred to colposcopy with minor abnormal cervical cytology low-grade squamous intraepithelial lesions (LSIL) and atypical squamous cells of undermined significance (ASC-US). The clinical performance of both tests was evaluated as stand-alone tests and combined, for detection CIN2+ and CIN3 over 2 years. Methods: ThinPrep â liquid-based cytol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 22 publications
3
32
0
4
Order By: Relevance
“…populations. A recent meta-analysis 6 of studies published between 2012 and 2017 demonstrated that dual-stained cytology was more specific than high-risk HPV testing for the identification of CIN2+; the relative specificity was 1.65 (95% CI: 1.42-1.92, P < .0001, n = 11 studies 8,14,15,[18][19][20][21][22][23][24][25] for the triage of ASC-US and 2.45 (95% CI:…”
Section: Resultsmentioning
confidence: 99%
“…populations. A recent meta-analysis 6 of studies published between 2012 and 2017 demonstrated that dual-stained cytology was more specific than high-risk HPV testing for the identification of CIN2+; the relative specificity was 1.65 (95% CI: 1.42-1.92, P < .0001, n = 11 studies 8,14,15,[18][19][20][21][22][23][24][25] for the triage of ASC-US and 2.45 (95% CI:…”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies reported the accuracy of p16, among which 1 study also evaluated dual staining. Eighteen studies evaluated the accuracy of dual staining only. The positivity criteria for p16 staining varied across the studies.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies used the nuclear scoring system of Wentzensen et al For 1 study, the p16 positivity cutoff was brown cytoplasmic staining for p16 in more than 10 cervical cells. With respect to dual staining, 19 studies considered simultaneous red nuclear and brown cytoplasmic staining of at least 1 cervical cell as a positivity criterion.…”
Section: Resultsmentioning
confidence: 99%
“…In triage of hrHPV-positive women with a negative cytology result, sensitivity for ≥CIN2 varies between 67% and 92%, with a specificity of 73-82% [36,37]. In triage of women with hrHPV-positive low-grade cytology, sensitivity and specificity of ≥CIN2 vary from 75-94% to 51-88%, respectively [38][39][40][41][42][43]. Limited studies have been performed with immediate p16/Ki-67 triage of hrHPV-positive women, without additional cytological interference.…”
Section: P16 /Ki-67 Dual-stainingmentioning
confidence: 99%